Adam Smith's Mixed Prudence and the Economy of the Public Sphere. (June 2016) - Randall, David
Jürgen Habermas argues that Adam Smith believed that men used a calculative form of reason in the economic realm. Yet it was not calculative reason, but a variety of forms of prudence that animated Smith's economic system. The individual exercise of prudence motivated mankind to labor, the collective exercise of prudence, expressed as supply and demand, disciplined mankind to labor where the disposition was lacking, and the combination of the individual and collective exercise of prudence allowed Smith's economic system to establish the norm of a just price. The pervasive importance of prudence in Smithian thought implies that the economy of the public sphere should be aligned with a latter-day form of traditional prudence rather than with systematized and calculative rationality. This re-conception implies that Habermas' democratic theory should be revised to consider free-market economic activity – and especially the process of price formation – one of those autonomous activities that comprise civil society, connect the lifeworld to democracy and require the protection of the democratic polity.